Epistemologi Kepemimpinan Transformasional: Telaah Komparatif antara Filosofi Pragmatisme dalam Pendidikan dan Model Servant Leadership - Herri Korneles; Andalangi Maatuil, Rexy; Rojer Efrat Mentaruk (Indo Publishing, 2025)
This article examines the epistemological foundations of transformational leadership through a comparison between pragmatic educational thought and the servant leadership model. Using a literature review approach, the article explores how both paradigms understand the sources of knowledge, the process of validating truth, and the moral implications for leadership practice. The study reveals that pragmatism places experience and reflection as the primary foundations for building knowledge. Truth is understood through practical benefits, problem-solving, and the ability to adapt to change. Servant leadership, on the other hand, emphasizes interpersonal relationships, morality, and service as epistemic resources that shape a leader's understanding of reality. Knowledge is born not only from empirical experience but also from sincerity, empathy, and a commitment to the well-being of others. The article's primary contribution is the formulation of the Pragmatic-Servant Epistemic Model (PSEM), an integration of experimental-reflective learning with a service-based epistemology. This model offers a new framework for educational leadership that demands both transformational capabilities and a strong moral orientation. This article is expected to enrich theoretical discussions and provide practical perspectives for educational leaders in facing the challenges of change and the need for humanization in learning environments.